Parametric Study on Incremental Wave Analysis for Jacket Platform in Malaysian Waters - Clayton, Corinna Omnie (Universiti Teknologi PETRONAS, 2018)
Offshore structures are often subjected to various environmental factors that can affect the integrity of the structure. Global overload due to wave-in-deck (WID) load is one of the factors that can plays a role in the reserve strength ratio of the platform. WID happens when there is insufficient wave crest to deck air gap causing sea water to enter the deck. Subsequently, the deck will experience excessive loadings. In this paper, incremental wave analysis (IWA) is used to analyse the trend of the structure responses when the waves are higher than the design waves. A software simulation using SACS had been performed by analysing the structure response subjected to wave with an incremental of 10%. It was found that the base shear for both 100-year design period and at structure collapse increases and directly influences the reserve strength ratio of the structure. Moreover, it was also found that the location of critical joints varies depending on the wave increment. Lastly, the trend for local displacement in the 45˚ direction is identified. The findings of this study can be use as quick check to identify critical joint when wave overtopping occur.